COVID-19, a challenge for inclusive education in Peru - Laderas Huillcahuari, Edison (2020)
In this research work, whose objective is to analyze the situation of COVID-19, as a challenge for inclusive education in Peru; whose approach is qualitative at a descriptive level, documentary research design, a document analysis technique was used whose sources of information were periodicals and scientific journals. In this educational political crisis in a state of health emergency, in the face of an invisible enemy COVID-19, students of different levels show difficulties in technological management, low internet signal in high Andean areas of Peru, lack of resources and equipment technological, both students and teachers. With a very precarious educational system and that is not only about talking about the inclusion of people with disabilities, it also has to do with integrating everyone according to their cultural diversity. Equity in education, then, must be based on the fact that education is a universal right with an inclusive opportunity for virtual education, therefore, it has to be based on equity, justice, tolerance and acceptance of the different ways of understanding and live reality.